FRI0164 Safety, Tolerability, And Functional Activity of ABT-122, A Dual TNF- and IL-17A–Targeted DVD-IG™, Following Single-Dose Administration in Healthy Subjects. (9th June 2015) - Mansikka, H.; Ruzek, M.; Hugunin, M.; Ivanov, A.; Brito, A.; Clabbers, A.; Cuff, C.; Hsieh, C.-M.; Okun, M.; Heuser, R.; Carter, D.; Hendrickson, B.; et al.
Abstract : Background: Several lines of evidence indicate that greater clinical efficacy and protection of joints may be possible in patients with RA by neutralizing TNF and IL-17 concurrently, compared with neutralizing either alone. ABT-122 is a novel Dual Variable Domain immunoglobulin (DVD-Ig™) protein incorporating two sets of selective binding domains, with one pair targeting TNF and one pair targeting IL-17A. Objectives: The safety, tolerability, and dual functionality of ABT-122 was investigated in a single ascending dose study in healthy subjects. Methods: This was a first-in-human, double-blind, placebo-controlled study with single dose ABT-122 administration by intravenous (IV) or subcutaneous (SC) route in 64 healthy volunteers. Each ABT-122 dose was evaluated in a group of 8 subjects, 6 receiving active drug and 2 receiving placebo. Groups 1 through 5 received ABT-122 at 0.1, 0.3, 1, 3, and 10 mg/kg IV, respectively, and Groups 6 through 8 received 0.3, 1, and 3 mg/kg SC, respectively. Dual binding capacity of ABT-122 for IL-17 and TNF in vitro was determined by sequential binding of human TNF and IL-17 to ABT-122 by surface plasmon resonance (SPR). Functional activity of recombinant ABT-122 or of serum from subjects receiving ABT-122 was determined using an in vitro assay of inhibition of TNF- and IL-17–induced IL-6 production by human fibroblast-like synoviocytes (FLS), derived from RA patients. Results: Following IV or SC administration there was no significant difference in the adverse event (AE) profile between subjects receiving ABT-122 or placebo. There were no serious AEs or premature discontinuations due to AEs reported in this study. No subject had an infusion reaction, systemic hypersensitivity reaction or an injection site reaction. No clinically relevant changes in laboratory parameters, vital signs, or ECG parameters occurred. All AEs were mild or moderate in intensity. The most frequently reported adverse event was upper respiratory infection for both subjects given ABT-122 or placebo. ABT-122 simultaneously bound a similar amount of TNF per ABT-122 molecule independent of the occupancy of the IL-17 binding sites and vice versa by SPR. ABT-122 in the functional assay fully inhibited IL-6 release from FLS stimulated by the combination of TNF and IL-17, whereas individual monoclonal antibodies only partially blocked the IL-6 production. Serum from subjects receiving ABT-122 demonstrated comparable potency (IC50 and IC90 ) to that defined by ABT-122 in the assay and was consistent across dose groups. Full neutralization was time- and dose-dependent through 21 days, and up to 10mg/kg, respectively. Conclusions: These data demonstrate that ABT-122 can simultaneously bind and neutralize TNF and IL-17 in vitro and functional levels of dual TNF and IL-17 inhibition with ABT-122 are maintained for up to three weeks after a single dose in healthy subjects. ABT-122 demonstrated an acceptable safety profile following single dose administration up to 3 mg/kg SC and 10 mg/kg IV. These study results support continued development of ABT-122 for immune mediated inflammatory diseases. Acknowledgements: Nancy Crosbie, Shekman Wong Disclosure of Interest: H. Mansikka Employee of: AbbVie, M. Ruzek Employee of: AbbVie, M. Hugunin Employee of: AbbVie, A. Ivanov Employee of: AbbVie, A. Brito Employee of: AbbVie, A. Clabbers Employee of: AbbVie, C. Cuff Employee of: AbbVie, C.-M. Hsieh Employee of: AbbVie, M. Okun Employee of: AbbVie, R. Heuser Employee of: AbbVie, D. Carter Employee of: AbbVie, B. Hendrickson Employee of: AbbVie, D. Pisal Employee of: AbbVie, S. Goss Employee of: AbbVie, J. Liu Employee of: AbbVie, C. Locke Employee of: AbbVie, N. Khan Employee of: AbbVie, R. Padley Employee of: AbbVie